2007
DOI: 10.1080/13676260701196103
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion and Marginalisation in Adolescence: The Experience of School Exclusion on Drug Use and Antisocial Behaviour

Abstract: Young people excluded from school are a group at an increased risk of drug use and antisocial behaviour during adolescence and later marginalisation and exclusion from society in adulthood. As part of the Belfast Youth Development Study, a longitudinal study of the onset and development of adolescent drug use, young people who entered post-primary school in 2000 (aged 11/12 years) were surveyed annually on four occasions. This paper reports on findings from this survey in relation to a supplementary group of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…School exclusion undermines student-teacher bonds and sense of connectedness to the school (Shochet et al, 2006) necessary to manage behaviour and enhance commitment to academic achievement (McEvoy & Welker, 2000). Social control theory (Hirschi, 1969) predicts an increase in antisocial behaviour following school exclusion because of reduced social (i.e., school) control, and empirical studies support this contention (Hemphill, Toumbourou, Herrenkohl, McMorris, & Catalano, 2006;McCrystal, Percy, & Higgins, 2007). Findings from this study are consistent with this research and suggest that exclusionary approaches should be reconsidered.…”
Section: School Environmentsupporting
confidence: 87%
“…School exclusion undermines student-teacher bonds and sense of connectedness to the school (Shochet et al, 2006) necessary to manage behaviour and enhance commitment to academic achievement (McEvoy & Welker, 2000). Social control theory (Hirschi, 1969) predicts an increase in antisocial behaviour following school exclusion because of reduced social (i.e., school) control, and empirical studies support this contention (Hemphill, Toumbourou, Herrenkohl, McMorris, & Catalano, 2006;McCrystal, Percy, & Higgins, 2007). Findings from this study are consistent with this research and suggest that exclusionary approaches should be reconsidered.…”
Section: School Environmentsupporting
confidence: 87%
“…Ecstasy users in this study also reported lower levels of communication with their parents and higher levels of disaffection with school. These patterns of behaviour were consistent with the high risk subsamples of the BYDS (McCrystal, Percy, & Higgins, 2007b). Researchers may believe that educating uninformed users of the risks associated with ecstasy will reduce its use, but whilst this assumption may prove too simplistic others suggest that ecstasy users may benefit from the dissemination of credible information to inform their use patterns and reduce the associated problems.…”
Section: ) Chi Square and P-valuesupporting
confidence: 65%
“…Such a suggestion is further supported by the demographic profile of the residential care sample, which was similar to the demographic profile of other vulnerable groups of young people participating in the BYDS; that is, school excludes (McCrystal et al, 2007a); young people attending Emotional and Behavioural Difficulty Units (McCrystal et al, 2007b); and early-onset drug users (McCrystal et al, 2006). A much more extensive empirical base exists on substance use behaviours and lifestyle patterns generally for these other vulnerable groups compared with young people living in residential state care.…”
Section: Discussionmentioning
confidence: 80%
“…However, there was no evidence for the existence of a third style of substance consumption*that is, ''problematic users'', identified by Newburn and Pearson (2002) as those who were drug dependent, typically on heroin or crack*but use of these substances was not explored in this paper. This substance consumption style was less likely to be detected among this age group generally, with use of ''harder'' drugs very limited among other vulnerable or at-risk groups participating in the BYDS (for example, McCrystal et al 2007aMcCrystal et al , 2007b.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation